A population study of factors associated with general practitioner consultation for non-inflammatory musculoskeletal pain. Issue 10 (1st October 2000) - Hagen, Kåre B; Bjørndal, Arild; Uhlig, Till; Kvien, Tore K
Abstract : OBJECTIVE: To investigate factors associated with visiting a general practitioner (GP) for non-inflammatory musculoskeletal pain, and to examine whether these factors were affected by duration (chronic v non-chronic) or location (widespread v regional) of pain. METHODS: From a cross sectional postal survey of 20 000 (response rate 59%) randomly selected adults in two counties of Norway, 6408 subjects who had experienced musculoskeletal pain during the past month were included. Patients who reported inflammatory rheumatic diagnoses made by a doctor were excluded. RESULTS: 2909 (45%) had consulted a GP for their musculoskeletal pain during the past 12 months. The odds of consulting were significantly increased by being a woman, by having a higher age and lower education, and by being a pensioner or on sick leave. Patients with widespread pain were more likely to consult than those with regional pain, as were patients with chronic compared with non-chronic pain. Greater than median pain intensity was the factor most prominently associated with consultation for men (odds ratio (OR)=2.4; 95% confidence interval (95% CI) 2.0 to 2.9) and for women (OR=2.6; 95% CI 2.3 to 2.9). Overall, consultation was significantly associated with mental distress for women but not for men. Subgroup analyses showed that consultation for chronic pain was significantly associated with greater than median mental distress for both women (OR=1.3; 95% CI 1.1 to 1.6) and men (OR=1.2; 95% CI 1.0 to 1.4), whereas consultation for non-chronic pain was not. CONCLUSION: The results show that about half of the patients with musculoskeletal pain consult a general practitioner (GP) each year, that demographic factors are associated with consulting, and that the role of mental distress for consulting a GP varies with duration of pain.